2021
DOI: 10.3390/ijerph18116144
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Bisphenol a Exposure, DNA Methylation, and Low Birth Weight: A Pilot Study in Taiwan

Abstract: Prenatal exposure to bisphenol A (BPA) may increase the risk of abnormal birth outcomes, and DNA methylation might mediate these adverse effects. This study aimed to investigate the effects of maternal BPA exposure on maternal and fetal DNA methylation levels and explore whether epigenetic changes are related to the associations between BPA and low birth weight. We collected urine and blood samples originating from 162 mother-infant pairs in a Taiwanese cohort study. We measured DNA methylation using the Illum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The associations between prenatal exposure to BPF and BPAF and 4-year-old children’s digit ratios remained significant in a smaller population in this study compared with our previous one (345 vs 545), suggesting the robustness of the feminizing effects of specific BPs. Recent studies have explored the role of DNAm between prenatal BPs exposure and children’s health, most of which measured DNAm in cord blood, peripheral blood, or other tissues of children. Placental DNAm, however, is more sensitive to EDC exposure with unique hypomethylated patterns . In this study, we found significant associations between prenatal BPF exposure and increased placental DNAm at FGF13 , and the hypermethylation of FGF13 was further associated with increased digit ratios in children at 4 years of age.…”
Section: Discussionmentioning
confidence: 53%
“…The associations between prenatal exposure to BPF and BPAF and 4-year-old children’s digit ratios remained significant in a smaller population in this study compared with our previous one (345 vs 545), suggesting the robustness of the feminizing effects of specific BPs. Recent studies have explored the role of DNAm between prenatal BPs exposure and children’s health, most of which measured DNAm in cord blood, peripheral blood, or other tissues of children. Placental DNAm, however, is more sensitive to EDC exposure with unique hypomethylated patterns . In this study, we found significant associations between prenatal BPF exposure and increased placental DNAm at FGF13 , and the hypermethylation of FGF13 was further associated with increased digit ratios in children at 4 years of age.…”
Section: Discussionmentioning
confidence: 53%
“…Finally, 127 pregnant women were excluded for lacking important covariate information and birth outcome data, and a total of 483 mother-child pairs were included in the final analyses. Low birth weight and preterm birth were defined as newborns with a birth weight <2500 g and gestational age at birth <37 completed weeks, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Despite no definitive mechanism to explain the effects of EDCs on birth outcomes, animal and epidemiological studies have demonstrated that exposure to bisphenols, parabens, and TCS is related to altered hormones (estrogen and thyroid-stimulating hormones), elevated levels of oxidative stress, and disturbances in lipid metabolism . Emerging evidence also suggests that DNA methylation and epigenetic changes induced by EDCs may help explain the adverse effects of intrauterine exposure to EDCs on placental function and fetal development. , It is well established that EDC levels in maternal serum and cord blood are highly relevant, implying that maternal EDC levels can be a signal for intrauterine exposure to some extent . In view of the short half-life of target EDCs and the poor reproducibility of urine, serum is more suitable for EDC exposure assessment and is capable of reducing the bias in the exposure assay …”
Section: Introductionmentioning
confidence: 99%
“…Epigenetics represents the distillation and integration of the exposures and the biological response implicated in stunting. Epigenetic regulation is essential for neurogenesis, brain function and behaviour, [4][5][6][7] it affects in-utero and postnatal growth, [8][9][10] it is central to nutritional metabolism [9][10][11][12][13][14] and immune function, 15 it responds to a wide range of environmental exposures, [16][17][18] and it determines longevity and the health trajectory across the life-course. [19][20][21] Stunting often begins before birth and there is a recurrent intergenerational component whereby women who were themselves stunted in childhood are at greater risk of bearing stunted offspring.…”
Section: What This Study Addsmentioning
confidence: 99%